ANALISIS UJI TEKAN BETON DENGAN BUBUK KARBON SEKAM SEBAGAI BAHAN SUBSTITUSI SEMEN - Prihanto, Amalyan; Setia Romadhon, Eri (JURNAL TEKNIK SIPIL-ARSITEKTUR, 2024)
In making concrete, local materials can be utilized so that the cost of making concrete is relatively cheap, in this study used carbon husk powder as a partial substitution material of cement in a concrete mixture and is expected to improve the quality of concrete and also environmentally friendly, the content of the carbon husk powder used namely 0%, 5%, 10%, 15% and 20% of the amount of cement used. The specimens were made with a composition of a mixture of 1 cement: 2 sand: 3 gravel, for the manufacture of normal concrete and the addition of carbon husk powder for the manufacture of concrete with a mixture of carbon husk powder with K-300 concrete quality. From the results of the study obtained the value of water use by using carbon husk powder increased in accordance with an increase in the composition of the carbon husk powder used, namely 0% (6.82), 5% (6.92), 10% (7.52), 15% ( 7,62) and 20% (8,82). The compressive strength of concrete using carbon husk powder at a composition of 5% shows that the average compressive strength of concrete is higher than normal concrete, which is 330,161 kg / cm2 (at 14 days), and lower 325,267 kg / cm2 (at 21 days) the compressive strength value of concrete continues to decrease with the addition of carbon husk powder composition as a cement substitution material at a composition of 10% (246,726 kg / cm2), 15% (226,513 kg / cm2) and 20% (166,350 kg / cm2) at 14 days and 10 % (268,027 kg / cm2), 15% (226,573 kg / cm2) and 20% (172,657 kg / cm2) at the age of 21 days.